Pengaruh PAD (Pendapatan Asli Daerah), Dana Perimbangan dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten Bandung Barat Tahun Anggaran 2012-2019 - Nova Rustiyani; Irene Sukma Lestari Barus (Jurnal Riset Akuntansi Politala, 2023)
This study will examine the effect of Regional Original Income, Balanced Funds, and Capital Expenditures on the financial performance of the West Bandung Regency Regional Government from the 2012 to 2019 fiscal year. The method of choice is scientific investigation using secondary data (time series data) collected over eight years in one location. Eviews Version 10 serves as a testing tool for error correction model (ECM) regression analysis. The findings of this study illustrate how Regional Original Income, Equalization Fund, and Capital Expenditure together affect Financial Performance and partially Regional Original Income does not have a significant effect on Financial Performance, Balance Fund has a significant positive effect on Financial Performance, and Capital Expenditure does not have a significant effect on Financial Performance.